A detailed quantitative outcome measure of glycosaminoglycans in human articular cartilage for cell therapy and tissue engineering strategies. Issue 12 (December 2015) - Kuiper, N.J.; Sharma, A.
Summary: Objective: Ideally, cartilage regenerative cell therapy should produce a tissue which closely matches the microstructure of native cartilage. Benchmark reference information is necessary to assess the quality of engineered cartilage. Our goal was to examine the variation in glycosaminoglycans (GAGs) in cartilage zones within human knee joints of different ages. Design: Osteochondral biopsies were removed from the medial femoral condyles of deceased persons aged 20–50 years. Fluorophore-Assisted Carbohydrate Electrophoresis (FACE) was used to profile GAGs through the superficial, middle and deep zones of the articular cartilage. Differences were identified by statistical analysis. Results: Cartilage from the younger biopsies had 4-fold more hyaluronan in the middle zone than cartilage from the older biopsies. The proportion of hyaluronan decreased with increasing age. Cartilage from the middle and deep zones of younger biopsies had significantly more chondroitin sulphate and keratan sulphate than the cartilage from older biopsies. This would suggest that chondrocytes synthesise more sulphated GAGs when deeper in the tissue and therefore in conditions of hypoxia. With increasing age, there was significantly more chondroitin-6 sulphate than chondroitin-4 sulphate. For the first time, unsulphated chondroitin was detected in the superficial zone. Conclusions: As an outcome measure, FACE offers the potential of a complete, detailed assessment of all GAGs and offers more information that the widely used 1, 9-dimethylmethylene blue (DMMB) dye assay. FACE could be very useful in the evolving cartilage regeneration field.